The Push for Asian American Native American Pacific Islander-Serving Institutions: Highlighting the Perspectives of Student Activists - Park, Julie J.; Dizon, Jude Paul Matias (The Journal of higher education (Columbus), 2022)
This paper documents the involvement of students who advocated for what eventually became the federal designation for Asian American and Native American Pacific Islander-Serving Institutions (AANAPISIs). Through interviews with 12 student activists, we document students' motivations for mobilizing, as well as the challenges they encountered. Students identified motivations such as gaining additional resources, seeking recognition through the legislation, and fostering proactive approaches to activism. Challenges included motivating their peers beyond immediate self-interest and the overshadowing of individual subgroup concerns within the broader Asian American and Pacific Islander community. We comment on the ways in which the push for AANAPISIs represents a racial project within a broader process of racial formation, and highlight both the possibilities and limitations of student advocacy.